Purchase, Pirate, Publicize: Private-Network Music Sharing and Market Album Sales - Jonathan Lee (Queen's University, Department of Economics, 2018)
I quantify the effects of private-network music sharing on aggregate album sales in the BitTorrent era using a panel of US sales and private-network downloads for 2,109 albums during 2008. Exogenous shocks to the network's sharing constraints address the simultaneity problem. In theory, private-network activity could crowd out sales by building aggregate file sharing capacity or increase sales through word of mouth. I find evidence that private-network sharing results in decreased album sales for top-tier artists, though the economic impact is quite modest. However, private-network activity seems to help mid-tier artists. The results are consistent with claims that word of mouth is stronger for lesser-known artists and that digital sales are more vulnerable to increases in file sharing capacity. I discuss policy implications and alternatives to costly legal efforts to shut down private file sharing networks.
Keywords: L82; L86; O34; 330; intellectual property; copyright; file sharing; piracy; digital music